Long Distance Relationship in Husband and Wife Couples in Bandar Lampung: Review on Maslahah Mursalah - Adi Saputra, Fahmi; Qodir Zaelani, Abdul; Hermanto, Agus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
In married life, husband and wife ideally live together in one place of residence so that they can carry out their authority and responsibilities as husband and wife to create a harmonious family. But it’s different with the implementation of the authority and responsibilities of husband and wife that occur in Sukarame Village, Bandar Lampung, where the husband does’nt live with his wife and childrens in one house because the husband works outside the city to earn a living or better families economy, which requires them not to live together for a period, which resulted in them not being able to lead a life together, leaving their wifes and children at home, and have a long distance relationship. The purpose of this study is to examine the exercise of authority and responsibility of husbands and wifes who don’t live together from the perspective of mas̲lah̲ah mursalah. This type of research is qualitative in the form of field research. The results of this study indicate that in Sukarame Village, Bandar Lampung, the authority and responsibilities of husband and wife do not live together, namely by calling each other or WhatsApp and video calls, although they still must meet face to face and transfer some money for their daily needs. From the point of view of mas̲lah̲ah mursalah, it is included in the interests of individuals or minorities and cannot be used as evidence because it only benefits the couple and therefore does not fulfill the conditions required by mas̲lah̲ah mursalah